APPLICATION OF ENVIRONMENTALLY ACCEPTABLE MICELLAR LIQUID CHROMATOGRAPHY IN PHARMACEUTICAL ANALYSIS - Šljivić, Jasmina; Milanović, Isidora; Tomić, Ljiljana; Mesarović, Aleksandra (ACADEMIC REVIEW, 2023)
The most commonly used method for pharmaceutical analysis is reverse-phase high-performance liquid chromatography. Micellar liquid chromatography represents an alternative to these methods due to the use of micellar mobile phases, which is extremely important from the aspect of green chemistry. This method uses the same columns, detectors and injectors as in traditional high-performance reverse-phase liquid chromatography methods. The aim of this paper is to present the properties of mobile and stationary phases used in micellar liquid chromatography with special reference to the proper selection of surfactants that enable the separation of the analyzed sample. The chromatographic behavior of the analyzed sample was also analyzed in detail, because in the presence of micelles, substances behave differently due to multiple interactions. The contribution of this work is also reflected in the provided clear presentation of the advantages, limitations and contemporary applications of micellar liquid chromatography.